Leadership in Wolf, Canis lupus , Packs - Mech, L. David (DigitalCommons@University of Nebraska - Lincoln, 2000)
I examine leadership in Wolf (Callis lupus) packs based on published observations and data gathered during summers from 1986 to 1998 studying a free-ranging pack of Wolves on Ellesmere Island that were habituated to my presence. The breeding male tended to initiate activities associated with foraging and travel, and the breeding female to initiate, and predominate in, pup care and protection. However, there was considerable overlap and interaction during these activities such that leadership could be considered a joint function. In packs with multiple breeders, quantitative information about leadership is needed.